1986
DOI: 10.1002/chin.198628018
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Aluminum/Cryolite Reference Electrodes for Use in Cryolite‐Based Melts.

Abstract: Two reference electrodes for use in cryolite‐based melts have been developed and te‐.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
1
1
Order By: Relevance
“…Overvoltages, ~, calculated from the impedance data and given in Table I, are also inconclusive. 2 The values for the overvoltages on platinum differ significantly from those reported by Thonstad (4) and, taken together with the observed differences in the IRe vs. I curves for the platinum and cermet anodes (Fig.…”
Section: Fig 2 Electrochemical Impedance Spectra For Platinum Anodecontrasting
confidence: 37%
See 1 more Smart Citation
“…Overvoltages, ~, calculated from the impedance data and given in Table I, are also inconclusive. 2 The values for the overvoltages on platinum differ significantly from those reported by Thonstad (4) and, taken together with the observed differences in the IRe vs. I curves for the platinum and cermet anodes (Fig.…”
Section: Fig 2 Electrochemical Impedance Spectra For Platinum Anodecontrasting
confidence: 37%
“…Recently Ohtsuka et al (2) reported an infrared study of a tungsten oxide film made by the electrochemical oxidation of tungsten in H2SO4 solution (aqueous). We report here the infrared spectral change in the entire mid-IR frequency range of 500-4000 cm 1 during electrochromic reactions of WO3 films made by a salt precipitation method.…”
Section: Discussionmentioning
confidence: 99%